Interface Stability Analysis of a Gel Material Surrounded by Air. Issue 1753 (24th February 2015) - Garavito Garzon, Carlos A.; Calderer, M. Carme.; Kumar, Satish
ABSTRACT: We study the stability of small amplitude harmonic perturbation at the interface of a gel material surrounded by air. The equations describing the system's dynamics are solved using classical perturbation methods. Assuming that the amplitude decays over time, we establish conditions for the system to return to its equilibrium state. The proposed model includes the effect of the boundary conditions and can be extended to more general situation in which the material is surrounded by an arbitrary fluid.